Mucinous cystadenoma of the appendix - Oktay Aydin; Faruk Pehlivanli; Gökhan Karaca; Gülçin Aydin; İsmail Özler; Çagatay Erden Daphan (Apollo Medicine)
Mucocele is a rare condition caused by the collection of mucus with in the lumen of the appendix. It accounts for 0.2%–0.3% of patients undergoing appendectomy procedure. In this article, we describe the case of a 53-year-old female patient who presented with pain in the right lower quadrant of the abdomen and a clinical pattern likely to a appendicitis. The patient was treated with appendectomy while avoiding perforation of the cyst. The histological specimen revealed mucinous cystadenoma with clear resection lines. The patient was discharged on the second day after surgery without any complications.